Serenity [videorecording (DVD)] - Knight, Steven, 1959-; Knight, Steven, 1959-; Knight, Steven, 1959-; McConaughey, Matthew, 1969-; Hathaway, Anne, 1982-; Clarke, Jason, 1969- (Universal Pictures Home Entertainment, 2019)
A fishing boat captain's life is thrown into disarray when his ex-wife suddenly appears begging him to save her and their son from her new abusive husband by taking him on a fishing trip and throwing him into the ocean to be eaten by sharks.